Eye Care Service Use and Associated Health-Seeking Behaviors Among Malawian Adults: Secondary Analysis of the Malawi Fifth Integrated Household Survey 2019-2020 - Thokozani Mzumara; Marios Kantaris; Joseph Afonne (JMIRx Med, 2024)
Abstract BackgroundThe use of eye care services varies among different population groups. ObjectiveThis study aimed to assess self-reported eye care use (ECU) and associated demographic factors among Malawian adults. MethodsThis study used secondary data from the Malawi Fifth Integrated Household Survey 2019-2020, a nationally representative survey. The study included 12,288 households and 27,336 individuals 15 years and older. We entered age, sex, level of education, residency (urban/rural), and chronic disease into a logistic regression model, and used a confusion matrix to predict the model’s accuracy. A P ResultsAbout 60.6% (95% CI 60.0%-61.2%) of those with eye problems accessed formal care 2 weeks before the survey date. A logistic regression model showed that ECU was positively associated with education compared to none (odds ratio [OR] 6.6, 95% CI 5.927-7.366; PPPPP ConclusionsSocial support, women empowerment, education, and mobile clinics are key strategic areas that would increase access to eye care in Malawi. Further studies can investigate ECU among the pediatric population.